The acute paraquat poisoning mortality (APPM) score to predict the risk of death in paraquat-poisoned patients. (3rd April 2022) - Chen, Chun-Kuei; Chen, Yen-Chia; Mégarbane, Bruno; Yeh, Ying-Tse; Chaou, Chung-Hsien; Chang, Chia-Hsun; Lin, Chih-Chuan
Abstract: Context: Mortality prediction in paraquat poisoning is a major issue since most prediction rules are inapplicable if the exact ingestion time cannot be determined and/or the serum paraquat concentration is not readily available, as in most countries. Therefore, we aimed to develop and validate a new prediction rule not requiring these two parameters. Methods: We designed a 10-year observational cohort study including all consecutive paraquat-poisoned patients managed in two Taiwanese hospitals. We built one cohort to define and one cohort to validate this prediction rule. Parameters independently related to mortality determined using a multivariate analysis were used to formulate the Acute Paraquat Poisoning Mortality (APPM) score. Results: Overall, 321 paraquat-poisoned patients were included, 156 in the derivation and 165 in the validation cohort. Mortality rates in the derivation and validation cohorts were 73% and 81%, respectively ( p = 0.20). The three parameters chosen of 28-day mortality at presentation were urine paraquat level >10 ppm (using a colorimetric sodium dithionite-based test; odds ratio (OR), 12.70; 95% confidence interval (CI), 2.64–61.24), white blood cells >13.0 G/L (OR, 5.50; CI, 1.41–21.48) and blood glucose >140 mg/dL [7.8 mmol/L] (OR, 7.45; CI, 1.70–32.86). In the derivation cohort, the area under the ROC curve (AUC-ROC) of the APPM score did not significantly differ from AUC-ROCs of serum paraquat (0.95, p = 0.25) and the Severity Index of Paraquat Poisoning (0.95, p = 0.33). AUC-ROCs of the APPM score in the derivation and validation cohorts were 0.91 and 0.94, respectively. Conclusion: We built and validated a reliable score to predict 28-day mortality in paraquat-poisoned patients at presentation, independently from the ingestion time and serum paraquat measurement.